Learning styles and perceived problem-solving ability of students in a baccalaureate physiotherapy programme. - Wessel J; Loomis J; Rennie S; Brook P; Hoddinott J; Aherne M (Physiotherapy Theory & Practice, 1999)
The purpose of this study was to determine the learning styles and problem-solving ability of physiotherapy students. The subjects were 158 students from years 2 to 4 of a baccalaureate physiotherapy programme. All subjects completed the Kolb Learning Style Inventory (LSI) and were classified into one of four learning styles. They also completed the Heppner Problem Solving Inventory (PSI), for which a total score and three subscale scores were calculated. Chi-square and one-way analyses of variance were used to determine differences between years for the LSI and PSI respectively. The association between the PSI and LSI was determined with an eta coefficient. The majority of students had the preferred learning style of 'assimilator' or 'converger'. The scores on the PSI were similar to those reported for other undergraduate students, and were not related to learning style. There were no significant differences between years for the LSI or the PSI score. We conclude that physiotherapy students in a baccalaureate programme prefer a learning style in which they combine abstract conceptualisation (thinking) with either reflective observation (watching and listening) or active experimentation (doing). Neither learning style nor perceived problem-solving ability was different across years.